DNSSEC: extensões de segurança para servidores DNS - Carvalho, Sérgio Luiz de (2013)
The purpose of this paper is to disseminate information about its features and capabilities of DNSSEC "Domain Name System Security Extensions", which is an extension of the DNS protocol that is responsible for a service resolution process names and Internet domains. In this context the importance of features because it motivates its use today, also addresses the vulnerabilities and security flaws found in the old DNS protocol, and describing why their unavailability may result in lack of services in the network. Therefore, this new technology DNSSEC it provides greater system security name resolution in reducing the risk of data manipulation and forged domains can help reduce many security problems faced by server administrators. Through this exploratory research is that we will perform a comparison of this new technology, seeking results that enable understanding of this topic.